A preliminary survey of the practice patterns of United States Guild Certified Feldenkrais PractitionersCM - Buchanan Patricia A (BMC, 2010)
Abstract Background The Feldenkrais Method® of somatic education purports to guide people of varying ages and abilities to improve function. Many people choose this method to aid with recovery from injury, manage chronic conditions, or enhance performance even though limited research supporting its safety and effectiveness exists to guide decisions about use and referral. Very little information about practitioner characteristics and practice patterns is publicly available to assist researchers in the design of appropriate safety and effectiveness studies. The purpose of this study was to obtain an initial overview of the characteristics of United States Guild Certified Feldenkrais PractitionersCM. Methods Of 1300 certified Feldenkrais® practitioners at the time of the study, there were 1193 practitioners with email accounts who were sent invitations to complete a web-based survey. The survey inquired about practice locations, additional credentials, service patterns and workloads during the previous 3 months. Response rate and descriptive statistics were calculated. Results The survey had a 32.3% (385/1193) response rate. The top states in which responders practiced were California (n = 92) and New York (n = 44). Most responders did not hold other credentials as traditional health care providers or as complementary and alternative medicine providers. Among those who did, the most common credentials were physical therapist (n = 83) and massage therapist (n = 38). Just over a third of traditional health care providers only provided Feldenkrais lessons, compared to 59.3% of complementary and alternative providers. On average, responders saw 7.6 ± 8.1 (median = 5) clients per week for individual lessons, 8.4 ± 11.5 (median = 5) clients per week for group lessons, and 2.9 ± 3.9 (median = 2) new clients per month for individual lessons. Conclusions This preliminary survey of United States Guild Certified Feldenkrais Practitioners indicated that most practiced in the west and northeast, did not hold additional credentials, and had part-time practices. Those who were traditional health care providers were more likely than complementary and alternative medicine providers in other areas to combine their services. These results provide a foundation for further analyses of Feldenkrais practitioner characteristics and practice patterns that can aid the design of safety and effectiveness studies, and enhance use and referral decision-making.